Akibat Hukum Perjanjian yang Tidak Dibuat Menggunakan Bahasa Indonesia - Hayati, Asna Nurul; Kusumadara, Afifah; Sulistyarini, Rachmi (Universitas Negeri Malang, 2021)
This study aimed to analyze the position of Law Number 24 of 2009 concerning the Flag, Language, State Emblem and National Anthem and Presidential Regulation Number 63 of 2019 concerning the Use of Indonesian Language and the legal consequences of agreements that were not made in Indonesian. The research approach used in this study was a statutory approach and a conceptual approach. Article 31 of the Language Law and Article 26 of Presidential Regulation Number 63 of 2019 required the use of the Indonesian language in every agreement making and were legally compelled. The obligation to use the Indonesian language in every agreement should be carried out. The legal consequences of agreements not made using the Indonesian language were regulated in Law Number 30 of 2004 concerning Notary Positions, which could be resolved on lex specialist derogat lex generalis. The agreement that remained binding has evidentiary power as a private agreement.